Green roof substrates—A literature review - Kader, Shuraik; Chadalavada, Sreenivasulu; Jaufer, Lizny; Spalevic, Velibor; Dudic, Branislav (Frontiers in Built Environment, 2022)
Green roofs are becoming increasingly popular in urban construction due to their wide array of benefits for creating a sustainable ecosystem. Many stakeholders invest in green roofs in the 21st century to enhance the environmental quality and mitigate urban ecological pollution. The substrate layer is the most important and critical component of green roof systems. The objective of the review study is to present the important information regarding the required elements that need to be considered for substrate selection of green roofs by critically reviewing the scientifically published articles. Research findings from past studies relevant to green roofs, vegetation and selective substrate parameters were extensively discussed under different topics related to water retention, drought resistance and related physico-chemical parameters. The generalities in past research articles were presented and special focus was provided on specific research articles those presented novelty regarding green roof substrates. Furthermore, the hotspots in all the considered research articles were commentatively identified and the appropriate solutions were evaluated. The critical review of published research articles indicates that most of the research on green roof substrates was conducted in either controlled laboratories or greenhouses and did not provide much importance to actual field tests. Therefore, these research findings are not sufficient to obtain the realistic field outcomes of the research. Future studies on green roof substrates should need to incorporate field experiments along with classical controlled tests by adhering to standard guidelines for assimilating climatic influences in substrates. Few studies have focused on dry climates, and further research needs to be conducted on dry climates due to their high susceptibility to drought and evapotranspiration. This manuscript would be the first review article that mainly focuses on substrates for green roofs, which is a novel aspect.